Aplikasi Segmentasi Huruf Jawa - Soephomo, Singgih Mardianto; -, Liliana; Budhi, Gregorius Satia (Jurnal Infra, 2015)
Javanese letter are a representative and a proof of Indonesiaâs rich and diverse. Nowadays the use of Javanese language in oral and written conversation Indonesia is getting rare. Our people prefer to learn our national language or international languages such as English and Chinese. Another work to conserve Javanese letter is make Javanese letter optical recognition. Therefore, in this thesis an application that could be used in the preprocessing phase of Javanese letter recognition was developed.Hough transform and projection profile are the methods that used in this application. Hough transform is a method that perform skew detection on the document. Projection profile is a method that process segmentation.In Chapter 5 light intensity, consistency range between rows, font size and type, the difference of font weight would affect the result. The result of projection profile method can segment 77% of document with consistent range between rows. The hough transform method can detect skew on the document up to 94%.